Religião Romana nas Fronteiras da Romanidade: um estudo sobre a construção e manutenção de identidades romanas durante o principado Júlio-Claudiano - Bondioli, Nelson de Paiva [UNESP] (2014)
This thesis is a study that aims at analyzing the relations between religion, politics and identity in the Roman world during the Julio-Claudian Principate. To that end we propose an assessment of the sacra publica in the city of Rome and the development of the imperial cults in the provinces, paying special attention to the worship of the living Princeps. To achieve the aims proposed by this study, we turn ourselves to the postcolonial theory and the vision that this critique brings to the comprehension of processes of identification, domination and manipulation of the symbols of power, considering its viability and importance to studies of Antiquity. Through an analysis of both the written and material sources concerning the period, we assert that it is possible to find parallel visions of Romanness, becoming necessary to displace Rome from its the traditional perspective, that the Romanness as seen by the elites of the city takes a central, hierarchical and imposing position to the entire Empire. Hence, we aim at understanding how Romanness was constructed and operated outside the urbs